Carinal trifurcation associated with isolated partial anomalous pulmonary venous return - Erdem, Semiha Bahceci; Yozgat, Yılmaz; YOZGAT, YILMAZ; Karkiner, Aytac; Nacaroglu, Hikmet Tekin; Can, Demet (My University, 2015)
Carinal trifurcation is described as an opening of the right upper lobe or accessory lobe close to the tracheal bronchus and carina. The etiology of these malformations has not been clearly understood since they commonly occur with cardiac anomalies resulting from their common embryonic development. Isolated partial anomalous pulmonary venous return with an intact atrial septum is a congenital anomaly where one or more of the pulmonary veins are connected to the venous circulation. To the best of our knowledge, the coexistence of a carinal trifurcation, tracheomalacia, and an isolated partial anomalous pulmonary venous return with an intact atrial septum has not yet been reported in the literature. In this article, we report the diagnostic approach and management of a seven-year-old girl with a delayed diagnosis and management of a coexisting carinal trifurcation, tracheomalacia, and an isolated partial anomalous pulmonary venous return with an intact atrial septum.